PENCAPAIAN “MALAKAH” PERSPEKTIF IBNU KHALD?N (Rumusan Aktualisasi Belajar dalam Tiga Domain: Kognitif, Afektif dan Psikomotorik) - Saeful Bahri (La-Tahzan: Jurnal Pendidikan Islam, 2020)
The concept of "malakah" as outlined by Ibn Khald?n in the Muqaddimah book is the construction of his thoughts on education. He places learning as a natural phenomenon for human civilization. The achievement of the malakah is formulated as the ability or behavior changes formed through the process of training with sincerity and complete mastery in the process of actualizing learning. Malakah means ownership that is rooted in the soul, not just understanding and memorization (cognitive) alone. To strengthen the achievement of malakah. Ibn Khald?n presented the theory of scientific discussion (al-mu??warah wa al-mun??arah) and the continuity of learning (itti??l) as supporters. It means that the learning formula as an optimization of the achievement of malakah developed by Ibn Khald?n is aimed at achieving three domains at once, cognitive, affective and psychomotor. At this level the meaning of malakah can be equated with professionalism for students.